Treatment Patterns of Biologic Disease-Modifying Antirheumatic Drugs and Janus Kinase Inhibitors in Patients with Rheumatoid Arthritis in Japan: A Claims-Based Cohort Study - Masahiko Miyashiro; Teita Asano; Yutaka Ishii; Celine Miyazaki; Hirohito Shimizu; Junya Masuda (Adis, Springer Healthcare, 2024)
Abstract Background Reports on treatment patterns of biologic disease-modifying antirheumatic drugs (bDMARDs)/Janus kinase inhibitors (JAKi) for rheumatoid arthritis (RA) in clinical practice are still sparse in Japan, especially in combination with conventional synthetic DMARDs (csDMARDs). Objectives The aim of this study was to investigate treatment patterns of bDMARD/JAKi in the treatment of RA in real-world clinical practice in Japan. Method A retrospective cohort study was conducted using the Japanese Medical Data Vision health claims database. The inclusion criteria required a recorded diagnosis of RA, defined by ICD-10 codes, in patients aged 18 years and older on the index date. We analyzed 39,903 RA patients treated with DMARDs from 2008 to 2020. Results Among analyzed subjects, 10,196 patients (25.6%) were prescribed bDMARDs/JAKi in combination with csDMARDs, and 3067 patients (7.7%) were prescribed these drugs without csDMARDs. Among the bDMARDs/JAKi, tumor necrosis factor inhibitors (TNFi) were the most commonly prescribed DMARD overall, and also the most common first-line therapy, accounting for 60.0% or 45.5% of patients prescribed these drugs in combination with or without csDMARDs, respectively. Switching, temporary discontinuation (restarting with the same agents), and discontinuation of bDMARDs/JAKi were observed in 3150 (30.9%), 1379 (13.5%), and 2025 (19.9%) patients with csDMARDs, and in 849 (27.7%), 513 (16.7%), and 833 (27.2%) patients without csDMARDs, respectively. Conclusions Real-world treatment trajectories of bDMARDs/JAKi with and without csDMARDs was analyzed in RA patients in Japan between 2008 and 2020. TNFi were the predominant first-line therapy, and likely to be switched to different classes. Understanding the current treatment patterns, including discontinuation, is important to find an optimal treatment strategy for RA patients.